Prevalence and incidence of neuropsychiatric disorders in post hospitalized COVID-19 patients in South America: a systematic review and meta-analysis - Perea-Flórez, Francisco; Javier-Murillo, Nair; Lapeyre-Rivera, André; Gamonal, Bryan; Cabanillas-Lazo, Miguel; Velásquez-Rimachi, Victor; Alva-Diaz, Carlos (Frontiers in Psychiatry, 2023)
There are multiple reports of neuropsychiatric disorders (NDs) such as stress, depression, post-traumatic stress disorder (PTSD) or anxiety, in patients who have survived the acute phase of COVID-19, being even more frequent in people who were hospitalized with moderate or severe disease.South America (SA) was one of the most affected continents during this time due to its health, social, political and economic context. We aimed to determine the prevalence and incidence of NDs in patients following hospitalization for COVID-19 in SA.We searched in PubMed, Embase, Scopus, Web of Science, LILACS, SciELO and Google Scholar databases up to October 2022. We performed proportion meta-analysis with a randomeffect model and Freeman-Tukey Double Arcsine transformation using the STATA 16.1 program. Finally, we evaluated heterogeneity by subgroup analysis and certainty of evidence with the GRADE approach.We included eight studies from four countries. We only pooled six studies with prevalence measures. The estimated prevalence of all NDs was 31.48% (two-studies, 95%CI: 25.82-37.43).Depression, anxiety, insomnia, PTSD and memory alterations had a pooled prevalence of 16.23% (three-This is a provisional file, not the final typeset article